How volatile and unpredictable are aid flows, and what are the policy implications? - Aleés Bulír; A. Javier Hamann (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This paper examines empirical evidence on the volatility and uncertainty of aid flows, and the main policy implications. Aid is found to be more volatile than fiscal revenues—particularly in highly aid-dependent countries—and mildly procyclical in relation to activity in the recipient country. These findings imply that the current pattern of aid disbursements is welfare-reducing. We also find that uncertainty about aid disbursements is large and that the information content of commitments made by donors is either very small or statistically insignificant. Policies to cope with these features of aid, as well as broader international efforts to reduce the volatility and procyclicality of aid, are briefly discussed.
Keywords: F35; O19; 330; external aid; volatility; predictability; IMF-supported programs; Entwicklungshilfe; Anpassungsprogramm des IWF